2019
DOI: 10.31331/jipva.v3i1.778
|View full text |Cite
|
Sign up to set email alerts
|

Pengintegrasian penilaian formatif dalam pembelajaran IPA berbasis saintifik terhadap pemahaman konsep peserta didik

Abstract: Tercapainya tujuan pembelajaran IPA dapat diketahui dengan melakukan penilaian yang merupakan salah satu prinsip pengembangan kurikulum 2013. Penelitian ini bertujuan untuk mengetahui pengaruh pengintegrasian penilaian formatif dalam pembelajaran IPA berbasis pendekatan saintifik terhadap pemahaman konsep peserta didik. Penelitian ini dilaksanakan di SMPN 3 Trenggalek kelas VIII tahun pelajaran 2017/2018 mata pelajaran Ilmu Pengetahuan Alam. Metode penelitian yang digunakan adalah quasy-experimental dengan des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
1
0
3
Order By: Relevance
“…It aligns with previous research, which shows that the formative assessment form is effective according to the needs of children and teachers and describes the development of children's abilities clearly and precisely (Simanjuntak & Mudiono, 2019). Supported by other research, the aim is to determine the effect of integrating formative assessment in science learning based on a scientific approach to students' conceptual understanding (Sari et al, 2019). The results found that the integration of formal and informal formative assessments in science learning based on a scientific approach had a significant influence on increasing students' understanding of concepts.…”
Section: Discussionsupporting
confidence: 81%
“…It aligns with previous research, which shows that the formative assessment form is effective according to the needs of children and teachers and describes the development of children's abilities clearly and precisely (Simanjuntak & Mudiono, 2019). Supported by other research, the aim is to determine the effect of integrating formative assessment in science learning based on a scientific approach to students' conceptual understanding (Sari et al, 2019). The results found that the integration of formal and informal formative assessments in science learning based on a scientific approach had a significant influence on increasing students' understanding of concepts.…”
Section: Discussionsupporting
confidence: 81%
“…3 (2020) perceptions, 16 the application of a critical review of the 2013 science teacher's book curriculum, 17 assessment instruments of science process skills performance, 18 problemsolving skills of science student, 19 and integration of formative assessment in science learning. 20 This research is different from previous research in terms of the subject and object, where the subject is elementary school students and the object is students' independence.…”
Section: Introductionmentioning
confidence: 79%
“…Pada pembelajaran bidang sains seperti pada bidang IPA dan Fisika, asesmen pembelajaran yang digunakan untuk mengukur hasil belajar siswa salah satunya adalah asesmen formatif (Ramadhani, 2021). Asesmen formatif ini merupakan suatu penilaian yang tidak memberikan skor kepada siswa, melainkan penilaian pembelajaran yang menekankan pada umpan balik yang dapat digunakan untuk memperbaiki pembelajaran (Sari et al, 2019).…”
Section: Pendahuluanunclassified